Biological insights from the premonitory symptoms of migraine. Issue 12 (December 2018) - Karsan, Nazia; Goadsby, Peter
Abstract Migraine is a common neurological disorder with a diverse clinical phenotype that comprises more than just head pain. Premonitory (prodromal) symptoms can start hours to days before the onset of a migraine headache and can predict its onset in some individuals. Such symptomatology can include lethargy, yawning, light and sound sensitivity, thirst and cravings. This earliest phase of the migraine attack provides valuable insights into the neurobiology of the disorder, furthering our understanding of how and why these phenotypically heterogeneous symptoms are mediated. Improvements in our understanding of migraine could provide novel therapeutic opportunities, with the possibility of closing the therapeutic gap that remains owing to a lack of sufficiently effective and well-tolerated acute and preventive treatments. Improved understanding of disease mechanisms and potential therapeutic targets through bench-to-bedside research into the premonitory phase is an exciting and emerging means of achieving this aim going forward. In this Review, we discuss the current evidence in the literature in relation to the phenotype and mediation of premonitory symptoms in migraine, and discuss the neurobiological insights gained from these studies. Premonitory symptoms of migraine can start hours to days before the onset of headache. In this Review, Karsan and Goadsby discuss the phenotypes of these premonitory symptoms and the insights that they provide into the neurobiology of migraine. Key points The premonitory stage of migraine occurs before the onset of migraine headache in adults and children and can predict headache onset. The prevalence of premonitory symptoms is probably underreported owing to a lack of patient and physician recognition and to misinterpretation of the symptoms as migraine triggers. Symptoms that can manifest during the premonitory phase can be broadly grouped as cognitive and mood changes, fatigue and changes in alertness, homeostatic and hormonal changes, and migrainous or sensory sensitivities. Correlation of premonitory symptoms with functional neuroimaging changes during this phase suggests vital involvement of subcortical and cortical areas, namely the hypothalamus, midbrain and limbic areas. Linking the clinical phenotype and neuroanatomy to the neurochemical systems in these brain areas has revealed neurotransmitters and neuropeptides that might mediate premonitory symptoms and contribute to migraine pathophysiology. Further research looking at agents that target the identified receptors could lead to novel targeted treatment options for migraine.